Haemodynamics and cerebral oxygenation of neonatal piglets in the immediate ex utero period supported by mechanical ventilation or ex utero oxygenator. (1st April 2021) - Darby, Jack R.T.; Berry, Mary J.; Quinn, Megan; Holman, Stacey L.; Bradshaw, Emma L.; Jesse, Sarah M.; Haller, Christoph; Seed, Mike; Morrison, Janna L.
Abstract : Key points: The margin of human viability has extended to the extremes of gestational age (<24 weeks) when the lungs are immature and ventilator‐induced lung injury is common. Artificial placenta technology aims to extend gestation ex utero in order to allow the lungs additional time to develop prior to entering an air‐breathing environment. We compared the haemodynamics and cerebral oxygenation of piglets in the immediate period post‐oxygenator (OXY) transition against both paired in utero measures and uniquely against piglets transitioned onto mechanical ventilation (VENT). Post‐transition, OXY piglets became hypotensive with reduced carotid blood flow in comparison with both paired in utero measures and VENT piglets. The addition of a pump to the oxygenator circuit may be required to ensure haemodynamic stability in the immediate post‐transition period. Abstract: Gestational age at birth is a major predictor of wellbeing; the lower the gestational age, the greater the risk of mortality and morbidity. At the margins of human viability (<24 weeks gestation) immature lungs combined with the need for early ventilatory support means lung injury and respiratory morbidity is common. The abrupt haemodynamic changes consequent on birth may also contribute to preterm‐associated brain injury, including intraventricular haemorrhage. Artificial placenta technology aims to support oxygenation, haemodynamic stability and ongoing fetal development ex utero until mature enough to safely transition to a true ex utero environment. We aimed to characterize the impact of birth transition onto either an oxygenator circuit or positive pressure ventilation on haemodynamic and cerebral oxygenation of the neonatal piglet. At 112 days gestation (term = 115 days), fetal pigs underwent instrumentation surgery and transitioned onto either an oxygenator (OXY, n  = 5) or ventilatory support (VENT, n  = 8). Blood pressure (BP), carotid blood flow and cerebral oxygenation in VENT piglets rose from in utero levels to be significantly higher than OXY piglets post‐transition. OXY piglet BP, carotid blood flow and carotid oxygen delivery (DO2 ) decreased from in utero levels post‐transition; however, cerebral regional oxygen saturation (rSO2 ) was maintained at fetal‐like levels. OXY piglets became hypoxaemic and retained CO2 . Whether OXY piglets are able to maintain cerebral rSO2 under these conditions for a prolonged period is yet to be determined. Improvements to OXY piglet oxygenation may lie in maintaining piglet BP at in utero levels and enhancing oxygenator circuit flow. Key points: The margin of human viability has extended to the extremes of gestational age (<24 weeks) when the lungs are immature and ventilator‐induced lung injury is common. Artificial placenta technology aims to extend gestation ex utero in order to allow the lungs additional time to develop prior to entering an air‐breathing environment. We compared the haemodynamics and cerebral oxygenation of piglets in the immediate period post‐oxygenator (OXY) transition against both paired in utero measures and uniquely against piglets transitioned onto mechanical ventilation (VENT). Post‐transition, OXY piglets became hypotensive with reduced carotid blood flow in comparison with both paired in utero measures and VENT piglets. The addition of a pump to the oxygenator circuit may be required to ensure haemodynamic stability in the immediate post‐transition period.